Amyloid‐beta plasma and cerebrospinal fluid biomarkers in aged dogs with cognitive dysfunction syndrome. (18th June 2020) - Stylianaki, Ioanna; Polizopoulou, Zoe S.; Theodoridis, Alexandros; Koutouzidou, Georgia; Baka, Rania; Papaioannou, Nikolaos G.
Abstract: Background: Cognitive dysfunction syndrome (CDS) is a common progressive neurodegenerative disease that is poorly defined. Specific multitargeted protocols do not exist for setting the diagnosis and the prognosis of the syndrome. Hypothesis/Objectives: To quantify Aβ42 and Aβ40 peptides in blood and cerebrospinal fluid (CSF) and to investigate their contribution to CCDS. Animals: A total of 61 dogs from a hospital population. Methods: Case‐control study. Six young (YG: 0‐4 years old), 8 middle‐aged (4‐8 years old), 17 cognitively unimpaired and aged (CU: 8‐20 years old), and 30 cognitively impaired and aged (CI: 8‐17 years). From the CI group, 10 dogs exhibited mild impairment (CI‐MCI) and 20 exhibited severe impairment (CI‐SCI). Cognitive status was assessed using a validated owner‐based questionnaire. Direct and indirect Aβ markers were determined in plasma fractions (total‐TP, free‐FP, bound to plasma components‐CP) and CSF using commercial ELISA assays (AΒtest, Araclon Biotech). Results: TPAβ42/40 facilitated discrimination between CI‐MCI and CU aged dogs with area under curve ≥ 0.79. CSFAβ42 levels were higher ( P = .09) in CU (1.25 ± 0.28 ng/mL) than in MCI (1.04 ± 0.32 ng/mL) dogs. CSF Aβ42 levels were correlated with the CP fragment (CPAβ40: P = .02, CPAβ42: P = .02). CPAβ42 was higher in the CI‐MCI (23.03 ± 11.79 pg/μL) group compared to the other aged dogs (CU: 10.42 ± 7.18 pg/μL, P = .02, SCI: 11.40 ± 12.98 pg/μL, P = .26). Conclusion and Clinical Importance: The Aβ should be determined in all of the 3 plasma fractions (TP, FP, CP). In the clinical approach, TPAβ42/40 could be used as an efficient preselection tool for the aged canine population targeting dogs with mild cognitive impairment.